Educational and Behavioral Counseling in a Methadone Maintenance Treatment Program in China: A Randomized Controlled Trial - Pulin Liu; Pulin Liu; Ranran Song; Yao Zhang; Cheng Liu; Bingxi Cai; Xuebing Liu; Jiaoyuan Li; Xueqin Chen; Juntao Ke; Jiao Lou; Wei Chen; et al. (Frontiers in Psychiatry, 2018)
IntroductionMethadone maintenance treatment (MMT) programs have been rapidly scaled up nationwide in China in recent years, and psychosocial intervention measures, including counseling, were recommended for improving the outcomes of MMT. However, the effectiveness of counseling in MMT programs remains controversial. This study investigated the efficacy of educational and behavioral counseling (EBC) mode in an MMT program in China.MethodsA total of 125 eligible participants were randomized to EBC or a control group. Patients in the EBC group received weekly, manual-guided, group educational counseling for 8 weeks and individual behavioral counseling for the next 8 weeks. Patients in the control group received standard methadone maintenance treatment as usual (TAU).ResultsDuring the 16-week trial, the EBC group showed better treatment attendance (P = 0.022) and a greater increase in knowledge regarding heroin addiction (P = 0.001) and MMT (P = 0.005) than did the TAU group. Between the two groups, there were no significant differences regarding drug abstinence and reduction of risky behaviors.ConclusionEBC affiliated with MMT improved patients’ cognition and adherence to treatment, facilitating their successful recovery.Clinical Trial RegistrationChiCTR-IOR-15006673: http://www.chictr.org.cn.